Successful Management of Quadruplet Pregnancy following Spontaneous Conception: A Rare Case Report - Shrestha, Deepak; Thapa, Babita; Aryal, Shreyashi; Shrestha, Buddhi Kumar; Panthee, Kiran; Kalakheti, Balkrishna (Journal of Lumbini Medical College, 2017)
Introduction: When more than two fetuses simultaneously develop in the uterus, it is called higher order multiple pregnancy. The incidence of such pregnancies ranges from 0.01% to 0.07%. Case report: We report a case of 26-year-old G2P1L0D2 with previous history of preterm vaginal twin delivery, diagnosed to have quadruplet pregnancy. She was admitted at 28 weeks of gestation for safe confinement. At 33 weeks of gestation, emergency cesarean section was conducted with outcome of two female and two male babies with quadriamniotic and quadrichorionic placenta, without any intra and post-operative complications. Conclusion: A multidisciplinary approach with good neonatal care facilities is warranted for a better outcome in higher order multiple pregnancies. DOI: https://doi.org/10.22502/jlmc.v4i1.88 Journal of Lumbini Medical College. 2016;4(1):46-9